2016
DOI: 10.4103/0974-7796.163799
|View full text |Cite
|
Sign up to set email alerts
|

An appraisal of a technical modification for prevention of bladder neck stenosis in retropubic prostatectomy: An initial report

Abstract: Objective:To report the experience with our technical modification of the trigone-bladder neck complex management in the prevention of bladder neck stenosis (BNS) following open simple retropubic prostatectomy.Materials and Methods:It was a retrospective review of data of patients that underwent open simple retropubic prostatectomy with technical modification of the trigone-bladder neck complex in two Nigerian tertiary hospitals, by a single surgeon, from January 2007 to December 2011. The data analysed includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Only two patients(2.8%) in this study were found to have cystoscopy con rmed bladder neck stenosis out of 72patients. This was not signi cant and this gure compares to reported incidence of bladder neck contractures where malament stitch was not used 17,18,19,20,21,22 . The reported incidence of bladder neck stenosis in these studies ranged from 1.7-6.3%.…”
Section: Discussionmentioning
confidence: 56%
“…Only two patients(2.8%) in this study were found to have cystoscopy con rmed bladder neck stenosis out of 72patients. This was not signi cant and this gure compares to reported incidence of bladder neck contractures where malament stitch was not used 17,18,19,20,21,22 . The reported incidence of bladder neck stenosis in these studies ranged from 1.7-6.3%.…”
Section: Discussionmentioning
confidence: 56%